Respostas
respondido por:
0
Resposta:
X'=1
X"=-3
Explicação passo-a-passo:
X³+2X-4=-2
Passa o -2 para o "outro" lado com sinal oposto
X³+2X-4+2=0
X³+2X-2=0
Faz ∆
∆=2²-4•(1)•(-2)
∆=4-4•(-2)
∆=4•4
∆=16
Faz bhaskara
X'=-b+√∆/2•a
X'=-2+√16/2•1
X'=-2+4/2
X'=2/2
X'=1
X"=-b-√∆/2•a
X"=-2-√16/2•1
X"=-2-4/2
X"=-6/2
X"=-3
respondido por:
1
Olá!
x³ + 2x - 4, para x = - 2
(- 2)³ + 2 · (- 2) - 4 =
- 8 + 2 · (- 2) - 4 =
- 8 + (- 4) - 4 =
- 8 - 4 - 4 =
- 8 - 8 =
- 16 ✅
Espero ter ajudado! :)
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás